Understanding the regulation of onion dormancy as influenced by deficit irrigation and postharvest storage regimes. - Ohanenye, Ikenna Christian (Cranfield University, 2019)
Onion (Allium cepa L.) is a biennial crop that produces a bulb in the first season only, but the demand for onion bulbs is all-year-round and to meet demand, they are stored for up to nine months. Consequently, this extended bulb storage causes premature sprouting, which impacts negatively on onion storage quality. Ethylene and 1-methylcyclopropene (1-MCP) were revealed to inhibit sprout growth in stored onion bulbs, whether applied independently or in combination. Also, higher abscisic acid (ABA) and fructans (especially, those at a higher degree of polymerisation) are reported to positively correlate with delayed sprouting. Moreover, the accumulation of ABA and fructans have previously been reported in other plants grown under water-stress. This study investigated (1) the the impact of deficit irrigation (DI) on sprouting; (2) the effects of DI on ABA and fructans contents, and redistribution, in relation to onion bulb dormancy and quality in store; and (3) the molecular mechanisms of fructans and sucrose metabolism in stored onion bulbs during onion dormancy break and sprouting. Across three seasons, onion cultivars ‘Red Baron’ sets, ‘Sherpa’ and double haploid (CUDH2107) seeds were grown and subjected to full irrigation (FI) (100% replacement of crop evapotranspiration) or deficit irrigation (DI) (50% of FI treatment) from bulb initiation to harvest. Bulbs were harvested at full maturity and stored at 1°C for five months and treated with or without 1-MCP (1 µL L⁻¹) for 24 h before storage under continuous ethylene supplementation (10 µL L⁻¹) or air. DI had no effect on dormancy- break, sprout emergence, total fructans and sugar content. Pre-harvest and end of curing ABA contents in the baseplate of DI bulbs was significantly higher compared to FI bulbs; however, no significant difference in sprouting between DI and FI bulbs was found. It was hypothesised that ABA accumulated under water-stress may not enhance onion dormancy. Ethylene and 1-MCP independently reduce the rate of ABA decline in stored onion bulbs. However, while ethylene was found to delay sprouting for both DI and FI bulbs, 1-MCP did not. This therefore questions the role of ABA in onion dormancy; nonetheless, bulbs treated with 1-MCP and stored under ethylene produced the shortest sprouts. Sucrose and fructans contents declined in sprouted bulbs while the expressions of the genes SPS (sucrose phosphate synthase), 1-SST (sucrose:sucrose 1- fructosyltranferase) and 6G-FFT (fructan:fructan 6G-fructosyltranferase) involved in sucrose and fructans biosynthesis were significantly upregulated. This suggested posttranslational regulations, or a higher catabolic rate compared to biosynthesis. The concentration of DP3-8 fructans were higher in top and bottom sections compared to the baseplate. Prior to sprouting, fructans of DPs 7-8 were no longer present in the top and bottom wedges, while they accumulated in the baseplate, irrespective of pre- or postharvest treatments. This redistribution of fructans within the bulb indicated a transition in dormancy state and could be used as a predictive marker for sprouting in stored onion bulbs. The application of this finding could significantly reduce onion bulb losses due to unpredictable sprouting during storage
Keywords: Allium cepa L.; dormancy; sprouting; fructans; non-structural carbohydrates; abscisic acid; abscisic acid glucose ester; 7' - hydroxy-abscisic acid; phaseic scid; dihydrophaseic acid